Attitudes toward plasmodium knowlesi malaria prevention behaviours among at-risk communities and health district officers’ efforts and challenges in promoting these behaviours: an elicitation study in peninsular Malaysia - Arina Anis Azlan,; Hazwani Damanhuri,; Mohammad Rezal Hamzah,; Hafizah Pasi,; Emma Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study explores at-risk communities’ attitudes toward Plasmodium knowlesi (P. knowlesi) malaria prevention behaviours using the Integrated Behavioural Model (IBM) as a guiding framework. This study also presents efforts and challenges faced by district health officers in Peninsular Malaysia in their role as the health authority for mitigating the disease. Seventeen informants were selected from at-risk areas in three states with high cases of P. knowlesi in 2019 (Johor, Pahang, Kelantan) to be interviewed. Semistructured interview questions were developed guided by the IBM framework. Three district health officers who were involved in malaria prevention efforts in the selected states were also interviewed. Qualitative data analysis using Atlas.ti 8 software was used to facilitate thematic coding. Five prevention behaviours were found to be prevalent among the informants and are hypothesised to be suited for behavioural improvement intervention among at-risk communities. The prevention behaviours identified are: consuming prophylaxis, wearing long sleeves, using bed nets, mosquito coils and insect repellent. Current efforts by health district officers for P. knowlesi malaria prevention include erecting warning signs, community education programmes, and empowering community influencers. Challenges faced by the health district officers include difficulty accessing remote locations, limited facilities, and military-specific issues. This study suggests that future prevention efforts focused on behavioural improvement among atrisk communities in Malaysia should concentrate on the five prevention efforts most prevalent among these communities.